Would Human-Robot Interaction Conferences Benefit From More Formal Reporting? Evaluating a Novel Study Reporting Form - Holthaus, Patrick; Rossi, Alessandra; Shrestha, Snehesh; Louie, Wing-Yue Geoffrey; Ucar, Aysegul; Garcia, Daniel Hernandez; Bagchi, Shelly (Ieee, 2025)
In an interdisciplinary and evolving research field like human-robot interaction, clear and precise results reporting is essential for study comparability and replicability. To address the lack of a standard for such reporting and, at the same time, provide guidance for novices in the field, we have developed a web-based reporting form to capture human-robot interaction studies, serving as a model for how conferences could adopt it into the submission pipeline. In this work, we present a formative evaluation of this form regarding its level of detail, format and clarity, and the perceived benefits for authors, reviewers, and the community as a whole. We report the expert review of nine researchers who highlight the substantial value of this tool. In addition, these experts also provide suggestions for improvements to its form and the addition of details surrounding qualitative reporting.
34th International Symposium on Robot and Human Interactive Communication-RO-MAN-Annual -- AUG 25-29, 2025 -- Eindhoven, NETHERLANDS